2020
DOI: 10.1002/lio2.360
|View full text |Cite
|
Sign up to set email alerts
|

Labyrinthine concussion: Historic otopathologic antecedents of a challenging diagnosis

Abstract: Objective: The term "labyrinthine concussion" has evolved to mean audiovestibular dysfunction in the absence of a temporal bone fracture (TBF). Despite a multitude of case descriptions of labyrinthine concussion, the precise pathophysiology remains poorly understood. Herein, we explore the historical otopathologic underpinnings of the diagnosis of labyrinthine concussion with a focus on the auditory pathway during the late 19th to the mid-20th centuries and conclude with a discussion of its contemporary releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…The pressure effects from mTBI will extend to the intralabyrinthine compartment and has historically been termed Labyrinthine Concussion (LC). Bartholomew and colleagues ( 4 ) recently published a historical review of the research into LC. In numerous animal studies and clinical reports dating back to the late 1800s, concussions have been reported to result in direct inner ear damage.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The pressure effects from mTBI will extend to the intralabyrinthine compartment and has historically been termed Labyrinthine Concussion (LC). Bartholomew and colleagues ( 4 ) recently published a historical review of the research into LC. In numerous animal studies and clinical reports dating back to the late 1800s, concussions have been reported to result in direct inner ear damage.…”
Section: Pathophysiologymentioning
confidence: 99%
“…1). The auditory nerve is particularly vulnerable to external force in the regions of the fundus of the internal auditory canal and the transitional zone (TZ) [36][37][38][39][40][41] . When the medial displacement of the brainstem is greater than that of the cochlea in the temporal bone, the resultant force on the auditory nerve may avulse the auditory neurons from the fundus of the internal auditory canal [36][37][38][39][40][41] .…”
Section: Causes Of Auditory Nerve Degeneration and Related Clinical Issuesmentioning
confidence: 99%
“…damage [36][37][38][39][40][41][42] . Clinically, cases in which the auditory nerve is damaged without damage to HCs are most suitable for cell transplantation because the HCs can provide trophic support, as mentioned above (Fig.…”
Section: Causes Of Auditory Nerve Degeneration and Related Clinical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The following data were collected from patients' medical records: sex, age, current medical history (course of disease, symptoms during attack, duration of attack, factors induced the attacks, triggering factors, and accompanying symptoms), underlying diagnosis (including labyrinthine infarction, dizziness/vertigo of unclear origin, vestibular neuritis, autoimmune inner ear disease, Ménière's disease, vestibular migraine, otitis media, vestibular paroxysmia, labyrinthine concussion, intralabyrinthine hemorrhage) (Figure 1), results of physical examination upon admission, and auxiliary examinations (such as immune-related laboratory tests, MRI and CT of the brain). Regarding the diagnosis of the above-mentioned underlying diagnosis, labyrinthine infarction, vestibular neuritis, labyrinthine concussion and intralabyrinthine hemorrhage are diagnosed according to patients' medical history, cochleovestibular evaluation and neurovascular imaging (8)(9)(10)(11), vestibular migraine, Ménière's disease and vestibular paroxysmia are diagnosed based on the diagnostic criteria suggested by Barany society (12)(13)(14), autoimmune inner ear disease is diagnosed according the medical history, vestibulocochlear evaluation and immune-related laboratory tests (15,16), otitis media is diagnosed according to the criteria reported by Gates et al (17).…”
Section: Clinical Data Collectionmentioning
confidence: 99%